Impact of adoption of better management practices and nutrition-sensitive training on the productivity, livelihoods and food security of small-scale aquaculture producers in Myanmar - Brako Dompreh, Eric; Rossignoli, Cristiano; Griffiths, Don; Wang, Quanli; Htoo, Khaing; Nway, Hsu Myat; Akester, Michael J.; Gasparatos, Alexandros (Springer, 2024)
Small-scale aquaculture is a major source of food in Myanmar. Beyond its importance for food security and nutrition, small scale aquaculture contributes to the livelihoods of many rural households and is a potentially valuable strategy for rural development. However, small-scale aquaculture producers have limited access to improved production technologies and information, which hampers the productivity and socioeconomic performance of small-scale aquaculture systems. In this study we assessed the impact of the adoption of better management practices and exposure to nutrition-sensitive training by 379 small-scale aquaculture producers in the Sagaing and Shan regions of Myanmar. We focused on whether and how the exposure to these interventions affected household food security through improvements in productivity and livelihoods. We used Propensity Score Matching to compare the performance of groups that were exposed to the intervention for one or two years, for seven impact variables. Exposure to the intervention had a positive effect for most impact variables, with differentiated effects among variables, group comparisons and regions. In terms of food security, beneficiaries had significantly higher dietary diversity (measured as the Food Consumption Score, FCS), but there were no significant differences for fish self-consumption (measured in kg/week). Longer exposure to the interventions produced significantly higher positive effects across most impact variables for the 2-year beneficiaries compared to 1-year beneficiaries and control groups. Our study suggests that the length of exposure to such interventions can be important in mediating the actual impact of small-scale aquaculture systems on household food security and livelihoods. Sustained help to small-scale producers should be considered in initiatives and development projects seeking to enhance the food security and rural development of small-scale aquaculture systems in Myanmar, and beyond.